Platelet Transfusion in Patients With Sepsis and Thrombocytopenia: A Propensity Score-Matched Analysis Using a Large ICU Database - He, Shuangjun; Fan, Chenyu; Ma, Jun; Tang, Chao; Chen, Yi (Frontiers in Medicine, 2022)
Purpose: Sepsis with thrombocytopenia is highly prevalent in critically ill intensive care unit (ICU) patients and is associated with adverse outcomes. Platelet transfusion is the primary treatment of choice. However, evidence for the beneficial effects of platelet transfusion in patients with sepsis and thrombocytopenia is scarce and low in quality. This study aimed to evaluate the association between platelet transfusion and mortality among ICU patients with sepsis and thrombocytopenia. Patients and methods: Using the Medical Information Mart for Intensive Care III database (v. 1.4), the outcomes of sepsis patients with platelet counts of ≤ 150,000/μL were compared between those who did and did not receive platelet transfusion. The primary outcomes were 28- and 90-day all-cause mortalities. The secondary outcomes were red blood cell (RBC) transfusion, ICU-free days, and hospital-free days. Propensity score matching was employed to assemble a cohort of patients with similar baseline characteristics. Results: Among 7765 eligible patients, 677 received platelet transfusion and were matched with 677 patients who did not receive platelet transfusion according to propensity scores. Platelet transfusion, as compared with no platelet transfusion, was associated with an increased risk of 28-day all-cause mortality (36.9% vs. 30.4%, odds ratio (OR), 1.21; 95% confidence interval (CI), 1.01–1.46; p = 0.039), increased risk of 90-day all-cause mortality (50.8% vs. 44.6%, OR, 1.13; 95% CI, 1.00–1.31; p = 0.048), fewer mean (standard deviation) 28-day ICU-free days (15.88 ± 8.97 vs. 18.64 ± 8.33 days, p < 0.001), and fewer hospital-free days (10.29 ± 8.49 vs. 11.43 ± 8.85 days, p = 0.017). The rate of RBC transfusion was not significantly different between the platelet transfusion and non-transfusion groups (p = 0.149). The results were maintained across several subgroup and sensitivity analyses. Conclusion: In this study, platelet transfusion was associated with higher 28- and 90-day all-cause mortalities. These results suggest the potential hazards of platelet transfusion in ICU patients with sepsis and thrombocytopenia.